REGISTER OF PATIENTS AS AN EFFECTIVE METHOD OF DIAGNOSING PRIMARY IMMUNODEFICIENCIES - L. P. Sizyakina; I. I. Andreeva (Педиатрическая фармакология, 2013)
It has been traditionally considered that primary immunodeficiency states (PID) are rare diseases. However, the incidence rate of PID in Europe is significantly higher than in Russia: our statistics on innate immunodeficiency morbidity is far from reality. Experience of establishing a register of PID patients in the Rostov Region proved that the combination of organizational and educational activities contributes to timely diagnostics, rational therapy and life quality improvement in patients with primary immunodeficiencies.